(untitled) (Constructionism Conference Proceedings, 2025)
This interactive workshop explores the transformative potential of effective questioning as a catalyst for student engagement and a key element in reimagining the curriculum, connecting it more deeply to the lives of learners. Participants will engage in practical activities, learning to craft questions that empower students to develop critical thinking, creativity, exploratory skills, and a sense of inquiry about the world around them. The workshop emphasizes how strategic questioning fosters active, engaged, and informed participation in situations and decisions that impact students’ lives. Grounded in the understanding that questions are fundamental to the teaching-learning process and crucial in all stages of Creative Learning, the session focuses on developing effective questions that promote constructionist education within regular classrooms.